Peningkatan kompetensi mahasiswa dalam hal komputasi dengan menggunakan kalkulator - Djadir Djadir; Ja’faruddin Ja’faruddin; Fajar Arwadi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The main goal of this program was to increasestudent competence in terms of computing using the software.This was intended to facilitate students in doing theirassignments, where they must perform a computationalprocess that emphasizes the result of a mathematical case. Theconstraints faced in general were the lack of internal teachingstaff who could guide the students in a frequent manner. As aresult, many students were unable to use the software properlyfor the computing process. Therefore, there was a need forconducting an educational and training program in order toovercome this issue. One of which was training in dataprocessing and analysis using Casio FX 991 ID Plus calculatorsoftware for students. This activity aimed to improve theability of students to use the Casio FX 991 ID Plus software.Specifically, this activity could develop students' ability to dothe computation to solve problems in various mathematicaltopics. The results achieved were that the participants weregenerally very enthusiastic in following the entire series ofactivities. The participants consulted with the presenters/facilitators of the training if they found problems and thingsthat were not yet known about the Casio FX 991 ID PlusCalculator. The result obtained from the training andindependent work was the participants have been able to dothe computing process well. It is recommended that the scopeof the implementation of such training program be furtherexpanded. In addition, according to the results and benefitsobtained from the implementation of the training, it isnecessary to implement the training for students and thecommunity, in general, to facilitate them in using Casio FX991 ID Plus Calculator as a tool for performing computingprocesses.